Ammonia-fed fuel cells: a comprehensive review. (July 2016) - Afif, Ahmed; Radenahmad, Nikdalila; Cheok, Quentin; Shams, Shahriar; Kim, Jung H.; Azad, Abul K.
Abstract: The use of an ammonia-fed solid oxide fuel cell (SOFC) is the most efficient method of generating power. In terms of CO2 emission, ammonia is a good indirect hydrogen storage material because it does not contain carbon and therefore will not release CO2 when used as fuel in a fuel cell or gas turbine. Using ammonia like hydrogen directly in a fuel-cell system provides high power density. Compared with other fuel cells, the ammonia-fed SOFC has many advantages. The availability of NH3 is one of the main reasons for the high output. This paper presents a comparative study of the working principles, analyses, applications, advantages and disadvantages of various technologies available for ammonia fuel cells. The aim of the paper is to review and describe the suitability of ammonia as a fuel for the next generation of fuel cells, including direct ammonia-fed SOFCs, the development of different types of fuel cells using ammonia as a fuel, and the potential applications of ammonia-fed fuel cells.